Role of maternal thyroid hormones in the developing neocortex and during human evolution - Stenzel, Denise; Huttner, Wieland B (Frontiers in Neuroanatomy, 2013)
The importance of thyroid hormones during brain development has been appreciated for many decades. In humans, low levels of circulating maternal thyroid hormones, e.g., caused by maternal hypothyroidism or lack of iodine in diet, results in a wide spectrum of severe neurological defects, including neurological cretinism characterized by profound neurologic impairment and mental retardation, underlining the importance of the maternal thyroid hormone contribution. In fact, iodine intake, which is essential for thyroid hormone production in the thyroid gland, has been related to the expansion of the brain, associated with the increased cognitive capacities during human evolution. Because thyroid hormones regulate transcriptional activity of target genes via their nuclear thyroid hormone receptors (THRs), even mild and transient changes in maternal thyroid hormone levels can directly affect and alter the gene expression profile, and thus disturb fetal brain development. Here we summarize how thyroid hormones may have influenced human brain evolution through the adaptation to new habitats, concomitant with changes in diet and, therefore, iodine intake. Further, we review the current picture we gained from experimental studies in rodents on the function of maternal thyroid hormones during developmental neurogenesis. We aim to evaluate the effects of maternal thyroid hormone deficiency as well as lack of THRs and transporters on brain development and function, shedding light on the cellular behavior conducted by thyroid hormones.